2016
DOI: 10.3171/2015.12.jns151552
|View full text |Cite
|
Sign up to set email alerts
|

Aneurysm growth and de novo aneurysms during aneurysm surveillance

Abstract: OBJECTIVE Many low-risk unruptured intracranial aneurysms (UIAs) are followed for growth with surveillance imaging. Growth of UIAs likely increases the risk of rupture. The incidence and risk factors of UIA growth or de novo aneurysm formation require further research. The authors retrospectively identify risk factors and annual risk for UIA growth or de novo aneurysm formation in an aneurysm surveillance protocol. METHODS Over an 11.5-year period, the authors recommended surveillance imaging to 192 patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…One explanation might be that, in the early stage following rupture, inflammation could play a protective role to remodel and seal the aneurysm wall, and during this early period aspirin's effect may not be protective. Another study of 192 patients harboring 234 unruptured IAs 35 showed that aspirin was protective for aneurysm growth (OR 0.72), but the findings did not reach statistical significance, potentially due to the small size of the cohort. On the other hand, in their multivariate analysis of 2334 patients, Hostettler et al 18 demonstrated that aspirin use was inversely associated with rupture (OR 0.65).…”
Section: Zanaty Et Almentioning
confidence: 97%
“…One explanation might be that, in the early stage following rupture, inflammation could play a protective role to remodel and seal the aneurysm wall, and during this early period aspirin's effect may not be protective. Another study of 192 patients harboring 234 unruptured IAs 35 showed that aspirin was protective for aneurysm growth (OR 0.72), but the findings did not reach statistical significance, potentially due to the small size of the cohort. On the other hand, in their multivariate analysis of 2334 patients, Hostettler et al 18 demonstrated that aspirin use was inversely associated with rupture (OR 0.65).…”
Section: Zanaty Et Almentioning
confidence: 97%
“…Apparently, as an aneurysm swells, the risk of subsequent rupture rises [51]. However, according to Serrone et al, the single predictor of aneurysm enlargement was the initial size of the lesion, with the annual risk of growth being evaluated at a mean of 3.5%, though higher for larger aneurysms [52]. The morphology of the aneurysm was also incriminated in influencing the risk of rupture, especially the formation of a daughter sac, the shape of the sac, and regions possessing a thinned arterial wall [53].…”
Section: Natural History Of Unruptured Aneurysmsmentioning
confidence: 99%
“…1,2,4 Aneurysm size is the most important risk factor followed by aneurysm configuration changes including aneurysm size progression. 4,5 In addition, the coexistence of an aneurysm-associated bleb, defined as an additional bulge on the aneurysm sac itself, is also described as a high risk factor for aneurysm rupture. [6][7][8] Based on radiologic flow models, the cause for such a bleb formation is thought to be the point of maximal wall shear stress within the aneurysm.…”
Section: Introductionmentioning
confidence: 99%